New Record of Mozambique Scorpionfish, Parascorpaena mossambica (Peters, 1855), (Actinopterygii: Order, Scorpaeniformes; Family: Scorpaendiae) From Indian Waters - Muddula Krishna Naranji; Govinda Rao Velamala; Kandula Sujatha (Marine Science Department Diponegoro University, 2017)
Parascorpaena mossambica is one of the rare species of Scorpaenidae in the Visakhapatnam coastal waters, India. Ten specimens are characterized by Dorsal fin IX 9; Anal fin III 5-6; Pectoral fin rays 15; Lateral line scales 43-44; Lateral line Pored scales 23-24; Lateral transverse scale scales 6-7/1/12-14; lachrymal bone with two lower strong antrose spines, anterior pointed and directed forward, tip reaching dorsal margin of upper lip, covered with skin; posterior one directed forward and slightly downward; suborbital with three spines. Only few records have been made in the whole Indian waters. Due to its rarity, P. mossambica is poorly studied and little known about their biology, ecology and distribution. In the present study provides additional data on this rare species. In particular, we describe its habitat, ecology, presence and distribution with several new records in Indian waters. Keywords: Scorpaenidae, fish, Parascorpaena mossambica, Visakhapatnam